Gut microbiota-driven neuroinflammation in Alzheimer’s disease: from mechanisms to therapeutic opportunities - Lei, Wenhui; Cheng, Yiwen; Liu, Xia; Gao, Jie; Zhu, Zhangcheng; Ding, Wenwen; Xu, Xiaocui; Li, Yating; Ling, Zongxin; Jiang, Ruilai; Chen, Xiaoying (Frontiers in Immunology, 2025)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by amyloid-beta (Aβ) plaques, tau hyperphosphorylation, and chronic neuroinflammation. While neuroinflammation—mediated by microglial and astrocyte activation—has long been considered a secondary response to Aβ pathology, emerging evidence positions it as a primary driver of cognitive decline. Notably, the gut microbiota, through the microbiota-gut-brain axis (MGBA), is crucial in modulating neuroinflammation. Dysbiosis disrupts gut barrier integrity, promotes systemic inflammation, and exacerbates neuroinflammatory responses, thereby accelerating AD progression. Recent advances reveal that gut microbiota-derived metabolites (e.g., short-chain fatty acids, lipopolysaccharides) directly influence microglial activation and Aβ aggregation. These findings have opened new therapeutic possibilities, with microbiota-targeted approaches such as probiotics, prebiotics, and fecal microbiota transplantation demonstrating promising neuroprotective effects in preclinical studies by reducing neuroinflammation and preserving cognitive function. However, translating these findings into clinical applications requires further validation through randomized controlled trials. This review summarizes the current understanding of gut microbiota-driven neuroinflammation in AD, from molecular mechanisms to potential therapeutic strategies. Targeting the MGBA represents a paradigm shift in AD management, emphasizing the modulation of neuroinflammation and pathological progression through gut microbiota interventions. The discussion also addresses existing research challenges and outlines future directions to advance this promising field.